2020
DOI: 10.3168/jds.2020-19068
|View full text |Cite
|
Sign up to set email alerts
|

Actions of putative embryokines on development of the preimplantation bovine embryo to the blastocyst stage

Abstract: Once it enters the uterus at d 4 to 5 after ovulation, the preimplantation bovine embryo is controlled in its development by regulatory signaling molecules from the mother called embryokines. Here, several cell-signaling molecules whose genes are expressed in the endometrium during d 5 to 7 after estrus were tested for the ability to affect the competence of the embryo for further development and the characteristics of the resultant blastocysts. Molecules tested were Cnatriuretic peptide (CNP), IL-8, bovine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
(77 reference statements)
0
19
0
Order By: Relevance
“…This gene was expressed by the morula (average TPM = 2.4) but at a lower level than for many other receptor genes. Nonetheless, treatment of bovine embryos with the prototypical ligand for NPR2, C-natriuretic peptide, caused an increase in number of cells in the inner cell mass of the blastocyst (Sang et al, 2020). Furthermore, some endometrial genes could be expressed in compartments of the endometrium (stromal cells or F I G U R E 5 Transcript abundance in the bovine morula for receptor genes using small molecules as ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene was expressed by the morula (average TPM = 2.4) but at a lower level than for many other receptor genes. Nonetheless, treatment of bovine embryos with the prototypical ligand for NPR2, C-natriuretic peptide, caused an increase in number of cells in the inner cell mass of the blastocyst (Sang et al, 2020). Furthermore, some endometrial genes could be expressed in compartments of the endometrium (stromal cells or F I G U R E 5 Transcript abundance in the bovine morula for receptor genes using small molecules as ligands.…”
Section: Discussionmentioning
confidence: 99%
“…In the cow, the focus of the current investigation, these molecules include IGF1 (Bonilla et al, 2011;Sirisathien et al, 2003), CSF2 (Loureiro et al, 2009), the WNT inhibitor DKK1 (Denicol et al, 2014), activin A (Kannampuzha-Francis et al, 2017) and IL6 (Wooldridge et al, 2019). Among the embryo functions regulated by embryokines are promotion of development to the blastocyst stage (Bonilla et al, 2011;Kannampuzha-Francis et al, 2017), protection from cell stress (Jousan & Hansen, 2007), and control of lineage commitment towards inner cell mass and trophectoderm (Denicol et al, 2014;Sang et al, 2020;Wooldridge et al, 2019). Some embryokines, such as CSF2 (Kannampuzha-Francis et al, 2015) and DKK1 (Tríbulo et al, 2017), have been reported to program development in a way that affects postnatal phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Less impressive improvements in ICM cell numbers could be seen when providing 1 and 10 ng/mL IL6 [ 49 ]. Sang et al did not detect a positive effect of IL6 on ICM numbers in bovine embryos [ 51 ]. They used an IL6 concentration of 50 ng/mL.…”
Section: Interleukinmentioning
confidence: 99%
“…Our previous research detected increases in EPI cell numbers when counting NANOG + nuclei, a marker for EPI cells [ 56 ]. However, another research group failed to detect changes in the number of NANOG + cells after treatment with 50 ng/mL IL6 [ 51 ].…”
Section: Interleukinmentioning
confidence: 99%
See 1 more Smart Citation